THE EFFECTIVENES OF MORINGA LEAVES AND YELLOW SWEET POTATO NOODLES FOR THE UTERINE INVOLUTION AND BREAST MILK PRODUCTION - Tuti Sukini; Sri Widatiningsih; Siti Rofi'ah (Poltekkes Kemenkes Semarang, 2021)
Background: Breast swelling or engorgement breast is the blocking up of breast milk because of the narrowing of the lactiferous duct or glands that are not emptied completely and the percentage incidence of it to postpartum women is 72%-85%. Breast swelling that is not handled properly can cause complications such as obstructions that lead to breast infection that can hinder the realization of exclusive breastfeeding in the future and without adequate treatment, the engorgement with moderate severity can become the obstructions of ducts and breast infections/mastitis. The purpose of this study is to determine the effect of the moringa leaves and yellow sweet potato noodles for the uterine involution and breast milk production of postpartum women.Methods: This research was conducted in the Tembarak Public Health Center, Temanggung Regency using a quantitative approach with Quasi Experiment method. The design was post test only with control group. The population in this study was postpartum women who gave birth in September and October 2016. The sampling technique used was total sampling.Results: The results of this study showed that there were effects from the consumption of moringa leaves noodles for breast milk production of postpartum women, showed by the p value of 0.034 and there was no effect from the consumption of yellow sweet potato noodles for the uterine involution, showed by the p value of 0.767.Conclusion: The suggestions for professional organizations were to cooperate with the relevant authorities (Health Offices) in disseminating the results of this evidence-based research to help increasing breast milk production by using local food, and also to cooperate in cross-programs and cross-sectors in order to incorporate the use of local food based on the evidence as a procedure in providing health education for postpartum women